1998
DOI: 10.1136/jcp.51.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of CD44v6 in metastases of intestinal and diffuse types of gastric carcinoma.

Abstract: Aims-To assess whether standard and variant isoforms of CD44 (CD44s, CD44v5, and CD44v6) have a diVerential expression profile in early versus advanced gastric adenocarcinoma of the diffuse and intestinal types and their metastases. Methods-Immunohistochemical expression of CD44s, CD44v5, and CD44v6 was evaluated in 14 early gastric cancers (nine intestinal and five diVuse) and 37 advanced adenocarcinomas (21 intestinal and 16 diffuse) as well as in 18 cases of perigastric lymph node metastasis. Ten normal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
1
16
1
Order By: Relevance
“…However, the direct role of CD44v in the metastatic process has remained obscure. It has been reported that CD44v6 in gastric cancer was related to tumor growth and metastasis, especially in lymph node metastasis (13,14). In our study, we demonstrated a significant relationship between CD44v6 expression and lymph node metastasis, lymphatic invasion, depth of invasion and stage by univariate analyses.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, the direct role of CD44v in the metastatic process has remained obscure. It has been reported that CD44v6 in gastric cancer was related to tumor growth and metastasis, especially in lymph node metastasis (13,14). In our study, we demonstrated a significant relationship between CD44v6 expression and lymph node metastasis, lymphatic invasion, depth of invasion and stage by univariate analyses.…”
Section: Discussionsupporting
confidence: 57%
“…It has been reported that CD44v6 is correlated with regulating tumor invasion, progression and metastasis in various kinds of malignancies including gastric cancer (11,12). In addition, CD44v6 was significantly correlated with lymph node metastasis in gastric cancer (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for such discrepancies is probably the comparison of results having different techniques [9] . T he cor relation between clinicopathological parameters and CD44 expression in the tumor is known to be different between intestinal and diffuse types of gastric carcinoma [29,30] . A study showed that the intestinaltype was more frequently CD44s-and CD44v6-positive than the diffuse-type tumor [15] , although the reactivity to these two antibodies did not correlate with histopathological and clinical prognostic factors in intestinal-type carcinoma [31] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CD44 isoforms containing variant exon 6 (CD44v6) is correlated with tumour invasion, progression and metastasis in various kinds of malignancies, including GC. [73][74][75] Lau et al 3 reported that CD44v8-10 is the major CD44 variant in GC and verified its role as a GCSC marker. The invasive and migratory capacities of the CD44(+) GC stem-like cells were much higher compared with those of the CD44(−) cells.…”
Section: Gcsc Surface Markersmentioning
confidence: 99%